1.
-4x^2 - 3 + 2x - x^2 - 4x + 5 = -5x^2 + 2 + 6x
2.
2 + 3x - x^2 - 2x^3 + 5x^3 - 4x^2 - 3x + 5 = 7 - 5x^2 + 7x^3
3.
4 - 2x - 3x^2 - 5x^2 + 2x - 3 - 5 + x + 4x^2 = -4 + x - 4x^2
4.
8 - 7x - x^3 + 4x^2 - 6x - 5x^2 - 2 + 10x - 4x^3 - 2x = 6 - 5x - 5x^3 - x^2
5.
7a^2 - 2ab + 3b^2 - 5a + 2b - 4a^2 + 3ab + 2b^2 - 4a + 3b =
8a^2 + ab - 9a + 5b
6.
4x^3 − 2y^3 + 5x^2y − 2xy^2 − 5x^3 + 2y^3 − 6xy^2 − 3x^2y =
-x^3 - 2x^y - 8xy^2
7.
x^3 + 4y^3 − 6x^2y − 2xy^2 − 3x^2y + 3xy^2 − 5x^3 − 3y^3=
- 4x^3 + y^3 - 9x^2y + xy^2